Discrepancies between archaeological and 14C-based chronologies: problems and possible solutions - Hans-Christoph Strien (Documenta Praehistorica, 2017)
14C dating of bone collagen is believed to produce the most reliable absolute dates for the Central European Early Neolithic, as the selection of bones in anatomical context minimises taphonomic problems. In contrast, a comparison of three newly published local or regional chronological models as well as a comparison of several series of dates from bone collagen, charcoal and cereals highlights problems probably caused by diagenetic influences, especially on collagen. Therefore, at least the checking of bone collagen 14C dates against charcoal or cereal dates from the same contexts seems to be indispensable.